The Use of Artificial Intelligence in Writing Classes: A Qualitative Study on the Perceptions of Lecturers and EFL - Ramadani, Ramadani; Pitaloka, Nova Lingga (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The research aims to understand two main aspects: lecturers’ perceptions of students’ use of AI in writing activities, and students’ own views toward these technologies. Using a qualitative research design, data were collected through semi-structured interviews with three lecturers and nine EFL students selected through purposive sampling. The researcher served as the primary instrument, engaging directly with participants to capture their authentic experiences. Data were analyzed using open thematic analysis to identify key themes and patterns emerging from participants’ responses. The findings reveal a nuanced understanding of AI’s role in writing education. Lecturers acknowledged the usefulness of AI in assisting students with grammar, organization, and idea generation but expressed concerns about excessive dependence, diminished creativity, and weakened critical thinking skills. Meanwhile, students appreciated AI tools such as Grammarly and ChatGPT for improving clarity, expanding vocabulary, and supporting brainstorming processes, yet noted that these tools occasionally misinterpreted topics or made their writing sound impersonal. Overall, both groups agreed that AI should function as a supportive aid rather than a substitute for human effort. The study concludes that the effective integration of AI in writing instruction requires clear pedagogical guidance, ethical awareness, and critical reflection to foster responsible and meaningful use in academic writing contexts.